Przesłanki nowelizacji Kodeksu karnego w zakresie wykonywania środków karnych świadczenia pieniężnego i nawiązki na cel społeczny oraz ocena jej skutków w ujęciu retrospektywnym - Politowicz, Konrad A. (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
The article is an attempt at a historical analysis of enactment of penal means when the sentenced obligation for a lawbreaker is to make a payment for compensation of social results of crimes. According to successive evolution of law regulations that have been in force in that matter, the author shows its weaknesses and advantages, concepts of following modifications, and thus reactions to such changes by the subjects who were the mentioned payment beneficiaries – including non-governmental organizations, in fact realizing systemic goals of compensative penal means. Basing on that background, the point of estimation is also the last and very important amendment of chapter VII of Penal executive code and art. 47 of Penal code in force since the 1 July 2011. This brought about the centralization of the system of executing the sentenced payments and expending resources thus gained, establishing as their only administrator the central Fund for supporting victims of crimes and post-penitentiary help. The consequences of the above-mentioned amendment were important for the accumulation of these funds and their accessibility for implementing the programs of supporting crime victims. The basic goals of the described reform were finally not achieved, even though the Fund was able to implement them with its budget income.
Keywords: Fundusz Pomocy Pokrzywdzonym oraz Pomocy Postpenitencjarnej; wykonywanie sankcji; kompensacja społeczna przestępczości; środki karne